European Union legislation for demand-side management and public policies for demand response - Machado, B. (2019)
Energy is now intrinsically linked to technological and social development, powering all such systems. The use of fossil fuels to supply the required energy is causing global environmental and health issues and is impacting on all life forms on the planet. Given the increasing energy use, anthropogenic greenhouse gas emissions are consequentially increasing. A critical and evolutionary way of thinking about the energy and resources demand management and supply is necessary because there is a clear concern about irreversible impacts on the world and a scarcity of the resources as well. At the same time, all the energy and resource use processes should be optimized to maximize the benefits, reduce the costs and promote stakeholders network, toward a circular economy. This could be the way to supply the demand without increasing the scarcity of the resources and to simultaneously achieve environmental benefits. At the same time, creating an educational grid is important to change the established paradigms, to promote critical thinking about the wasted resources and thinking holistically about overall consumption. This paradigm shift is changing the market, making it more competitive and reducing inefficiency by promoting the efficient use of resources. In the XXI century, legislation and public policies which consider sustainability approaches are constantly improving, trying to fix the pathways to avoid climate changes and achieve energy efficiency, but at the same time, the energy and resources demand still increasing to a no sustainable way to the social and environmental aspects.